Respuesta :
Answer:
The value of the Rational expression when [tex]x=-2[/tex] is: [tex]-7[/tex]
Step-by-step explanation:
For this exercise is important to remember:
- When a negative number is raised to an even power, the result will be positive.
- The multiplication of signs:
[tex](+)(+)=+\\(-)(-)=+\\(-)(+)=-[/tex]
Then, given the following Rational expression:
[tex]\frac{2x^2+5x+9}{x^2+2x-1}[/tex]
You need to follow these steps in order to find its value when [tex]x=-2[/tex]:
1. Substitute the given value of "x" ([tex]x=2[/tex]) into the expression:
[tex]\frac{2(-2)^2+5(-2)+9}{(-2)^2+2(-2)-1}[/tex]
2. Evaluate and simplify:
[tex]\frac{2(4)+5(-2)+9}{4+2(-2)-1}=\frac{8-10+9}{4-4-1}=\frac{7}{-1}=-7[/tex]